Socio-demography, nutritional status and physical activity among elderly in Samarahan division, Sarawak, Malaysia - Mohd Fakhree Bin Saad; Cheah Whye Lian; Helmy Hazmi (Intelektual Pustaka Media Utama, 2021)
The physical activity among elderly has been associated with reduction of risk from all-cause mortality and improve physical, mental, and social well-being. The objectives were to determine the physical activity status among elderly in Samarahan Division, Sarawak and its association with socio- demographic characteristics and nutritional status. A cross-sectional study was carried out on 199 elderly, aged between 60 to 90 years, from rural area in Samarahan Division (Asajaya and Simunjan district), Malaysia. Socio-demographic characteristic was taken via questionnaire, nutritional status and body composition of the elderly was measured using anthropometric measurement, and physical activity using pedometer. Data were analyzed using IBM SPSS version 26. The proportion of physically active among elderly was 12.6% and mean daily steps are 3946 steps (SD=1669 steps). Multiple linear regressions revealed that age, body mass index (BMI), and sex were significant associated with physical activity. Lack of physical activity among elderly remain a problem. Understanding these predictors related to physical activity is important for designing intervention program.